Application Of Learning Science Concepts Through Sunan E-Learning - Fakhriyah, Fina; Masfuah, Siti; Hilyana, Farah Shoufika (Jurnal Basicedu, 2021)
The purpose of writing this article is to describe the application of LMS (Sunan) in learning the concept of science in the Primary Teacher Education Study Department Universitas Muria Kudus before the covid-19 pandemic and after the covid-19 pandemic. Internet-based learning allows synchronous learning to occur with the main advantage that the learner and facilitator do not have to be in the same place. The use of Sunan helps to learn in a remote context and is limited to not meeting face to face during this covid-19 pandemic. In this era of e-learning, lecturers have an important role in using Moodle to support e-learning activities. The benefits of using e-learning are that it can be accessed easily, the cost is more affordable, the learning time and insight becomes external because of the learning resources obtained from various sources.